2016
DOI: 10.1063/1.4945628
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics simulation study of successive hydrogenation reactions of carbon monoxide producing methanol

Abstract: Doing ab initio molecular dynamics simulations, we demonstrate a possibility of hydrogenation of carbon monoxide producing methanol step by step. At first, the hydrogen atom reacts with the carbon monoxide molecule at the excited state forming the formyl radical. Formaldehyde was formed after adding one more hydrogen atom to the system. Finally, absorption of two hydrogen atoms to formaldehyde produces methanol molecule. This study is performed by using the all-electron mixed basis approach based on the time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Alternatively, carbon formed by equation R2 can react with H2 or H or CO, initiating the formation of the precursors CH and C2O, leading to the formation of complex organics as well as methane. Literature studies determined that in the ground-state CO + H reaction has a barrier of about 4 kcal/mol ( (Pham et al 2016) and references therein) and concluded that HCO formation must occur in CO* excited state, leading all the way to the formation of H2CO and CH3OH (not observed in our experiments).…”
Section: Volatile Organics Formationsupporting
confidence: 48%
See 1 more Smart Citation
“…Alternatively, carbon formed by equation R2 can react with H2 or H or CO, initiating the formation of the precursors CH and C2O, leading to the formation of complex organics as well as methane. Literature studies determined that in the ground-state CO + H reaction has a barrier of about 4 kcal/mol ( (Pham et al 2016) and references therein) and concluded that HCO formation must occur in CO* excited state, leading all the way to the formation of H2CO and CH3OH (not observed in our experiments).…”
Section: Volatile Organics Formationsupporting
confidence: 48%
“…The gas-phase HCO radical has also strong absorption at 2434 cm -1 (Jacox 2004). Although its formation from H2 and CO would not be surprising (Pham, et al 2016), its persistence at 1473 K in the chamber and subsequently on the sapphire window at room temperature is unlikely. One explanation is that HCO could be etched into the sapphire window and trapped through chemisorption.…”
Section: High Temperature Photochemical Formation Of Solid Refractory...mentioning
confidence: 97%
“…In subsections 3.1, 3.2, and 3.3, we describe the treatment of real-space variables by means of NAOs and an efficient method of computing the response function. Moreover, we report the methods to realize AIMD simulations and the frozen-phonon approximation for the normal-mode coupling coefficients (20) in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In interstellar clouds, small dusts covered with ice provide substrates to produce simple organic molecules, where chemical reactions proceed efficiently compared to gas phase . The reaction of H+CO→HCO is the first step towards the production of simple organic molecules such as H 2 CO and CH 3 OH . This reaction is considered important on ice surfaces to reproduce the observed abundance of these molecules .…”
Section: Introductionmentioning
confidence: 99%